(untitled) (Mustansiria Dental Journal, 2018)
Objective: To analyzes and determines the prevalence of type of denture fracture in four hospitals. Method: Data were collected from patients who attended prosthodontic clinics for denture repairs at four hospitals. For each patient requiring of a fractured complete and partial denture, the variables were recorded: causes of denture fracture, the type of fracture and the history of previous recurrent fractures. Results: Of 560 repaired denture 330 (59%) were complete dentures, 160 (30%) were removable partial denture, which were excluded from the study, and 70 (10%) involved replacement of the teeth that had debonded from the denture bases. The ratio of upper to lower complete denture fractures was approximately 2:1, most of the fractured dentures (65%) were those of males. Poor fit appeared to be the main cause of denture fracture 120 (20%), and poor occlusion was the second most common case recorded 50 (8%) .Midline fracture was the most common type of fracture during the period of study 210(40%). Most of fracture the fractured dentures 180 (32%) had previously been repaired once or more. Conclusion: The total number of complete denture fractures was considerably enhanced by repetitive fractures, which can be reduced by the application of prosthetic principles in constructing and maintaining dentures particular during the laboratory stages. Improvements in the processing techniques and the type of resin can reduce the incidence of denture fracture .Various polymers have been developed for use as denture base resins to overcome some of the mechanical deficiencies of polymethylmethacrylate .